Al2O3 modified Yb2Si2O7 material for environmental barrier coating on surface of hot end component as well as preparation method and application of Al2O3 modified Yb2Si2O7 material

By doping Al2O3 in Yb2Si2O7 and synthesizing Al2O3 modified Yb2Si2O7 material, the problem of the surface protective film of SiCf/SiC ceramic matrix composite is solved, and the densification of the material and the improvement of high-temperature corrosion performance are achieved.

CN119707531AActive Publication Date: 2025-03-28NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411669389.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-28
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

When SiCf/SiC ceramic matrix composite materials are in service under high temperature, gas erosion, high temperature corrosion and complex stress conditions, the SiO2 protective film generated on the surface is prone to react with water vapor, resulting in high porosity and poor density of the material, which in turn affects its service performance and life.

Method used

By doping Al2O3 in Yb2Si2O7, the Al2O3 modified Yb2Si2O7 material is synthesized by solid-phase reaction combined with sintering process, improving the density of the material and its high-temperature CMAS corrosion resistance.

Benefits of technology

The generated Al2O3 modified Yb2Si2O7 material has lower porosity and higher density, which can effectively hinder CMAS penetration, improve its resistance to high-temperature corrosion in harsh service environments, and extend the service time of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707531A_ABST
    Figure CN119707531A_ABST
Patent Text Reader

Abstract

The invention discloses an Al2O3 modified Yb2Si2O7 material for an environmental barrier coating on the surface of a hot-end component as well as a preparation method and application of the Al2O3 modified Yb2Si2O7 material, and belongs to the field of environmental barrier coatings. According to the material, the Al2O3 modified Yb2Si2O7 material is synthesized by combining a solid-phase reaction with a sintering process, and the obtained material simultaneously contains two components, namely Yb2Si2O7 and Yb3Al5O12. Compared with undoped Yb2Si2O7, the doped material is more compact and has lower porosity and higher density, and Yb3Al5O12 is generated at high temperature after doping, so that the high-temperature corrosion resistance of Yb2Si2O7 is effectively improved, the service time is prolonged, and good application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmental barrier coatings on the surfaces of aviation engines, and in particular relates to an Al2O3-modified Yb2Si2O7 material for environmental barrier coatings on the surfaces of hot end components, and a preparation method and application thereof. Background Art

[0002] With the increasing requirements for thrust-to-weight ratio of new generation aircraft engines, the service temperature requirement has reached 1400℃ and above, and traditional nickel-based high-temperature alloys can no longer meet their needs. f / SiC ceramic matrix composites, due to their excellent high-temperature mechanical properties and high specific strength, have become a popular candidate material for the hot end components of the new generation of aircraft engines with a thrust-to-weight ratio of 15-20.

[0003] When serving in an environment with actual high temperature, gas erosion, high temperature corrosion and interactive coupling of complex stress conditions, SiC f A protective SiO2 protective film will be formed on the surface of SiC ceramic matrix composite materials. However, this dense silicon oxide protective film will react with water vapor to generate volatile silicon hydroxide mainly composed of Si(OH)4. Continuous volatilization will consume the surface material and leave a large number of pores and cracks that are conducive to corrosion, affecting the service performance and life of the material.

[0004] In order to improve the service reliability of CMCs in this service environment, researchers have proposed the concept of environmental barrier coating (EBC). In the EBC system, rare earth monosilicates represented by ytterbium monosilicate (Yb2SiO5) have low silicon activity and therefore have good high-temperature resistance to water vapor and CMAS corrosion. Unfortunately, the thermal expansion coefficient of rare earth monosilicates is quite different from that of the substrate and the silicon bonding layer, which causes the coating to crack due to mismatched thermal expansion deformation at high temperatures, affecting the service performance. Although the disilicates represented by ytterbium disilicate (Yb2Si2O7) have a thermal expansion coefficient that matches the substrate, their large silicon activity does make them easy to react with corrosive media, leaving fatal holes on the surface, which is not conducive to long-term service. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a preparation method and application of Al2O3-modified Yb2Si2O7 material for environmental barrier coating on the surface of hot end components. Specifically, by doping Al2O3 in Yb2Si2O7, it can not only improve the shortcomings of high porosity and poor density of the ceramic material itself, but also increase the material's resistance to high-temperature CMAS corrosion, so that it can play a good role in protecting the substrate under service conditions.

[0006] In order to solve the problems of the prior art, the present invention adopts the following technical solutions:

[0007] A method for preparing an Al2O3-modified Yb2Si2O7 material for a hot end component surface environmental barrier coating comprises synthesizing the Al2O3-modified Yb2Si2O7 material by a solid phase reaction combined with a sintering process, specifically comprising the following steps:

[0008] Step 1, preparation of Yb2Si2O7 powder raw materials:

[0009] According to the weight ratio of 3.2784:1, Yb2O3 and SiO2 powder raw materials were weighed, and then put into a ball mill, with 99.9% pure anhydrous ethanol as the medium, and ball milled for 24 hours to obtain a mixed powder of Yb2O3 and SiO2;

[0010] Step 2, Yb2Si2O7 powder synthesis:

[0011] The ball-milled Yb2O3 and SiO2 mixed powders were placed in a muffle furnace for solid phase reaction to synthesize Yb2Si2O7 powder;

[0012] Step 3, Yb2Si2O7 powder mixed with Al2O3:

[0013] Weigh Yb2Si2O7 powder and Al2O3 powder raw materials according to a weight ratio of 97:3, then put them into a ball mill, use 99.9% pure anhydrous ethanol as a medium, and ball mill for 24 hours to obtain a mixed powder;

[0014] Step 4, preparation of ceramic block of Al2O3-modified Yb2Si2O7 material:

[0015] The mixed powder is crushed and passed through a 180-mesh sieve, and a 5wt% PVA solution is added after the sieve, so that the concentration of the PVA after mixing is 8wt%, and the mixture is pressed to obtain a ceramic block;

[0016] Step 5, sintering of Al2O3 modified Yb2Si2O7 ceramic block:

[0017] The ceramic block is first subjected to a debinding treatment in a muffle furnace, and then subjected to high-temperature sintering in the muffle furnace to obtain Al2O3-modified Yb2Si2O7 material.

[0018] As an improvement, the temperature of the solid phase reaction in step 2 is 1500°C and the reaction time is 10 hours.

[0019] As an improvement, the pressing process in step 4 is to pressurize twice, the first pressurization is 200 MPa and maintained for 1 minute, and the second pressurization is 160 MPa and maintained for 30 seconds.

[0020] As an improvement, the process of debinding treatment in step 5 is to keep the temperature at 550°C for 2.5 hours.

[0021] As an improvement, the high temperature sintering process in step 5 is to keep the temperature at 1400°C for 10 hours.

[0022] The Al2O3 modified Yb2Si2O7 material prepared by the above preparation method is prepared from Yb2O3 powder, SiO2 powder and Al2O3 powder, the powder purity of the powder is ≥99.9%, and the Al2O3 modified Yb2Si2O7 material for the environmental barrier coating on the surface of the hot end component of the aircraft engine contains the phases of Yb2Si2O7 and Yb3Al5O 12 , density is 5.9335g / cm 2 , the porosity is 4.15%.

[0023] The above-mentioned hot end component surface environmental barrier coating Al2O3 modified Yb2Si2O7 material is used in the field of aviation engine environmental barrier coating.

[0024] Beneficial effects:

[0025] Compared with the prior art, the Al2O3-modified Yb2Si2O7 material for the environmental barrier coating on the surface of the hot end component of the present invention and its preparation method and application have the following advantages:

[0026] 1. The Al2O3 modified Yb2Si2O7 material prepared by the present invention is conducive to the formation of ytterbium aluminum garnet (Yb3Al5O 12 ) phase, which promotes the densification of the sample and helps to reduce the porosity of the material.

[0027] 2. After long-term CMAS corrosion at 1300°C, the Al2O3-modified Yb2Si2O7 material prepared by the present invention has low porosity and dispersed dense ytterbium aluminum garnet, which will effectively hinder CAMS penetration and enhance its high-temperature corrosion resistance as an EBC layer in harsh service environments.

[0028] 3. The present invention dopes Al2O3 into Yb2Si2O7. Compared with undoped Yb2Si2O7, the doped material is denser, has lower porosity and higher density. At the same time, Yb3Al5O 12 It will effectively improve the high temperature corrosion resistance of Yb2Si2O7, increase its service time, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The powder XRD pattern of the Yb2Si2O7 powder prepared in step 2 of Example 1;

[0030] Figure 2XRD pattern of Al2O3-modified Yb2Si2O7 material prepared in Example 1;

[0031] Figure 3 A schematic diagram of the surface morphology of the Al2O3-modified Yb2Si2O7 material prepared in Example 1;

[0032] Figure 4 It is a comparison diagram of the porosity of Example 1 and Comparative Example 1;

[0033] Figure 5 Schematic diagram of the morphology of Example 1 and Comparative Example 1 after 4 hours of CMAS corrosion. DETAILED DESCRIPTION

[0034] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0035] Example 1

[0036] An Al2O3-modified Yb2Si2O7 material for a hot end component surface environmental barrier coating, comprising an Al2O3-modified Yb2Si2O7 material synthesized by a solid phase reaction combined with a sintering process,

[0037] The preparation method of the Al2O3-modified Yb2Si2O7 material for the environmental barrier coating on the surface of the hot end component of the aircraft engine comprises the following steps:

[0038] Step 1, preparation of Yb2Si2O7 powder raw materials:

[0039] Weigh Yb2O3 and SiO2 powder raw materials according to the weight ratio of 3.2784:1, then put them into a ball mill, use 99.9% pure anhydrous ethanol as the medium, and ball mill for 24 hours;

[0040] Step 2, Yb2Si2O7 powder synthesis:

[0041] The ball-milled Yb2O3 and SiO2 mixed powders were placed in a muffle furnace for solid phase reaction to synthesize Yb2Si2O7 at a reaction temperature of 1500°C and a reaction time of 10 h.

[0042] Step 3, Yb2Si2O7 powder mixed with Al2O3:

[0043] Using an analytical balance, weigh Yb2Si2O7 powder and Al2O3 powder raw materials according to a weight ratio of 97:3, then put them into a ball mill, use 99.9% pure anhydrous ethanol as the medium, and ball mill for 24 hours;

[0044] Step 4, preparation of ceramic block of Al2O3-modified Yb2Si2O7 material:

[0045] The mixed powder is crushed and passed through a 180-mesh sieve, and after sieving, a 5wt% PVA solution is weighed and mixed with it, and the concentration of PVA after mixing is 8wt%. Subsequently, a hydraulic press is used to prepare ceramic blocks. The specific briquetting process is to pressurize 200MPa for 1 minute, and then pressurize 160M Pa for 30 seconds; the mixed powder is crushed and passed through a 180-mesh sieve, and after sieving, a 5wt% PVA solution is added, and the concentration of PVA after mixing is 8wt%. The mixture is pressed to obtain a ceramic block.

[0046] Step 5, sintering of Al2O3 modified Yb2Si2O7 ceramic block:

[0047] The prepared ceramic block is first subjected to a debinding treatment in a muffle furnace, with specific process parameters of maintaining the temperature at 550°C for 2.5 hours; after debinding, it is subjected to high-temperature sintering in a muffle furnace, with specific process parameters of maintaining the temperature at 1400°C for 10 hours.

[0048] Comparative Example 1

[0049] Except that Al2O3 is not added in step 3, the rest is the same as in Example 1.

[0050] Performance Testing

[0051] The materials prepared in each step of Example 1 were analyzed, and the results were as follows: Figure 1-3 As shown, Figure 1 The Yb2Si2O7 powder prepared in step 2, Figure 2 This is the XRD pattern of the Al2O3-modified Yb2Si2O7 material prepared in Example 1. Figure 3 This is the surface morphology of the Al2O3-modified Yb2Si2O7 material prepared in Example 1. It can be seen from the figure that the sample surface is dense and has fewer voids and cracks.

[0052] The porosity of the Al2O3-modified Yb2Si2O7 material prepared in Example 1 and the material prepared in Comparative Example 1 was measured. The results are as follows: Figure 4 As shown, the porosity of Comparative Example 1 and Example 1 are 28.7% and 4.15%, respectively.

[0053] The prepared Al2O3 modified Yb2Si2O7 ceramic block was subjected to a CMAS corrosion test to observe the morphology after corrosion. The specific operation was as follows: the surface area of ​​the ceramic block was measured using a vernier caliper at 30 mg / cm 2 Weigh the CMAS powder with the content of CMAS and evenly coat it on the ceramic block. Place the sample in a muffle furnace, raise the furnace temperature to 1300℃ at a heating rate of 4℃ per minute, and then keep it warm for 4 hours; after the insulation, lower the furnace temperature to room temperature at a cooling rate of 4℃ per minute, take out the sample, and observe the surface morphology.

[0054] The results are as follows Figure 5 As shown, the surface morphology of the material prepared in Example 1 after the CMAS corrosion test is as shown in Figure 5 (a) shows the cross-sectional morphology. Figure 5 (b) As shown; the surface morphology of the material prepared in Comparative Example 1 after CMAS corrosion test is as follows Figure 5 (c) shows the cross-sectional morphology. Figure 5 (d) as shown.

[0055] like Figure 5 (a) Figure 5 As shown in (c), after 4 hours of CMAS corrosion test, a large amount of residual CMAS exists on the surface of Example 1, indicating that the modification of Example 1 can delay the penetration of CMAS; a large amount of apatite, a corrosion product, exists on the surface of Comparative Example 1, and there are a large number of voids, indicating that Comparative Example 1 is severely corroded.

[0056] like Figure 5 (b) Figure 5 (d) After 4 hours of CMAS corrosion test, there is a residual CMAS layer on the top of Example 1, and the reaction layer is relatively thin; in Comparative Example 1, CMAS has fully reacted with the material, and there are a large number of voids.

[0057] In summary, the Al2O3-modified Yb2Si2O7 material for the hot end component surface environmental barrier coating prepared by the present invention has higher density and better resistance to CMAS corrosion, and can meet the material selection requirements of the environmental barrier coating material.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing Al2O3-modified Yb2Si2O7 material for environmental barrier coating on the surface of hot end components, characterized in that: The method comprises the following steps: Step 1, preparation of Yb2Si2O7 powder raw materials: According to the weight ratio of 3.2784:1, Yb2O3 and SiO2 powder raw materials were weighed, and then put into a ball mill, using 99.9% pure anhydrous ethanol as the medium, and ball milled for 24 h to obtain a mixed powder of Yb2O3 and SiO2; Step 2, Yb2Si2O7 powder synthesis: The ball-milled Yb2O3 and SiO2 mixed powders were placed in a muffle furnace for solid phase reaction to synthesize Yb2Si2O7 powder; Step 3, Yb2Si2O7 powder mixed with Al2O3: Yb2Si2O7 powder and Al2O3 powder were weighed in a weight ratio of 97:3, and then put into a ball mill, using 99.9% pure anhydrous ethanol as a medium, and ball milled for 24 h to obtain a mixed powder; Step 4, preparation of ceramic blocks of Al2O3-modified Yb2Si2O7 materials: The mixed powder is crushed and passed through a 180-mesh sieve, and a 5 wt % PVA solution is added after the sieve, so that the concentration of the PVA after mixing is 8 wt %, and the mixture is pressed to obtain a ceramic block; Step 5, sintering of Al2O3 modified Yb2Si2O7 ceramic block: The ceramic block is first subjected to a debinding treatment in a muffle furnace, and then subjected to high-temperature sintering in the muffle furnace to obtain Al2O3-modified Yb2Si2O7 material.

2. The method for preparing an Al2O3-modified Yb2Si2O7 material for an environmental barrier coating on a hot end component surface according to claim 1, characterized in that: The temperature of the solid phase reaction in step 2 is 1500°C and the reaction time is 10 h.

3. The method for preparing an Al2O3-modified Yb2Si2O7 material for an environmental barrier coating on a hot end component surface according to claim 1, characterized in that: The pressing process in step 4 is two pressurizations, the first pressurization is 200 MPa and maintained for 1 min, and the second pressurization is 160 MPa and maintained for 30 s.

4. The method for preparing an Al2O3-modified Yb2Si2O7 material for an environmental barrier coating on a hot end component surface according to claim 1, characterized in that: The process of debinding treatment in step 5 is to keep the temperature at 550°C for 2.5 hours.

5. The method for preparing the Al2O3-modified Yb2Si2O7 material for the environmental barrier coating on the surface of the hot end component according to claim 1, characterized in that: The high temperature sintering process in step 5 is to keep the temperature at 1400°C for 10 h.

6. Al2O3 modified Yb2Si2O7 material prepared by any one of the preparation methods described in claims 1-5, characterized in that: The invention is prepared from Yb2O3 powder, SiO2 powder and Al2O3 powder, wherein the powder purity of the powder is ≥99.9%, and the Al2O3 modified Yb2Si2O7 material for the environmental barrier coating on the surface of the hot end component of the aircraft engine contains the phases of Yb2Si2O7 and Yb3Al5O 12 , density is 5.9335 g / cm 2 , the porosity is 4.15%.

7. Application of the Al2O3-modified Yb2Si2O7 material according to claim 6 in the field of environmental barrier coatings for aircraft engines.

Citation Information

Patent Citations

  • Segmented environmental barrier coating systems and methods of forming the same

    CA3001202A1

  • Single-crystal rare earth disilicate material with strong CMAS corrosion resistance and preparation method of single-crystal rare earth disilicate material

    CN118186585A

  • Ceramic material for high-temperature water-oxygen environment and preparation method thereof

    CN119100791A

  • METHOD FOR ELECTROPHORESIS COATING OF A COMPOSITE MATERIAL PART WITH AN ENVIRONMENTAL BARRIER

    FR3084377A1

  • Protective coating for oxide ceramic based composites

    US20060024528A1